PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS III SD NEGERI 011 SIDOREJO KECAMATAN SIMPANG KANAN - Patimah '; Lazim. N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is the low learning outcomes IPA Elementary School third-grade students 011 Sidorejo ie with an average of 61.95 with KKM 65. This is because the teacher is still less varied in using models or strategies in the learning process that resulted in the current active students are less involved learn. The study is in the form of classroom action research (PTK). This study aims to improve learning outcomes IPA Elementary School third-grade students 011 Sidorejo. The formulation of the problem